IMPLEMENTATION OF DIGITAL LITERACY IN SOCIAL SCIENCES EDUCATION ELEMENTARY SCHOOL WITH WAYANG MEDIA FOR STKIP BINA INSAN MANDIRI PGSD STUDENTS - Zuni Eka Tiyas Rifayanti; Evi Rizki Salamah (Universitas Sebelas Maret, 2018)
Digital literacy referred to in the study here is the use of information technology as an alternative learning resource to support student literature in elementary school social studies courses and the use of puppet media in teaching puppet material Indonesian independence figures. The rapid development of information technology requires us to be able to use it for educational purposes. If the world of education can make good use of information technology, it is not impossible, the development of education will be better. One of the uses of information technology is the use of Digital Literacy in the learning process. This type of research is descriptive research with qualitative and quantitative approaches. From the results of the research that has been done and by looking at the discussion above, it can be seen that there is an increase and success in the application of a digital literacy culture in the scope of the STKIP Bina Insan Mandiri PGSD Study Program. The results of this study indicate that students who are able to carry out digital literacy and are accustomed to literacy have been proven from the test results and observations obtained by researchers.